Nabycie przedsiębiorstwa oraz połączenia i podziały spółek a ewidencja księgowa dla celów podatku dochodowego - Krzeszowski, Wojciech Dawid (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
Corporate accounting records should be kept in a way that enables drawing up a financial statement in compliance with the balance sheet law and defining an income (loss) as well as the amount of the tax due f/r the given fiscal year. There are a number of issues that arise related in connection with achieving this objective. They also arise in the case of acquisitions, mergers, and split-ups of companies. The paper presents selected comments on the accounting records in the aforementioned situations. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1178, s. 70-75